"The Economic Impact of European Union Membership on Poland, Romania and Croatia since their EU Accession : A Political Economy Perspective" - Bedoshvili, Nikoloz (2025)
This thesis explores the economic and political effects of European Union (EU) membership on three post-communist countries: Poland, Romania, and Croatia. Since their EU accession in 2004, 2007, and 2013 respectively, these countries have experienced significant economic transformations, institutional shifts, and policy realignments. The study applies a comparative political economy approach to evaluate how EU membership influenced key areas such as economic development, trade expansion, foreign direct investment (FDI), and national sovereignty. By focusing on the intersection of economic indicators and institutional change, the thesis investigates how EU integration has shaped policy alignment, governance structures, and the role of national governments in the policymaking process. It draws on the theoretical frameworks of neofunctionalism and intergovernmentalism to interpret the dynamics of integration.